A study of leadership qualities that effect organization performance. - Che Halim, Siti Sarah (2012)
Leader is a person who guides others toward a common goal, creating an environment in which other team members feel actively involved in the entire process. Leaders also are the decision makers so they are free to take decision and leader sometimes must consult with the team on decision that would be made. Effective leader posses certain qualities and generally can be classified into three broad categories: who leaders ARE (values, motives, personal traits, character); what leaders KNOW (skills, abilities, traits); and what leader DO (behaviors, habits, styles, competencies). The ARE-KNOW-DO approach to leadership has received enormous attention and investment in the ongoing attempt to upgrade leader. Admired leaders not only learn how to act, but also act in ways that ensure result. Therefore the qualities of leader are important to increase competitiveness and productivity leaders with the knowledge, skill, and behavior in order to success and be effectiveness through organization performance. Other than that, Malaysia also need good leaders that can adapt all the new skills in equipping themselve; with the new landscape also need to improve standard and qualities of industry in Malaysia in a better stages and must be strengthened to be the next engine of growth, other than that leader should have knowledge to creating result and attribute to be a successful organization. The kind of behavior and attitude among leader are need to be improve in term to get the best result, if the attitude of leader increase, performances of companies will increase, also it will attribute to the successful leadership in Malaysia. The theoretical contributions of this research lie in the following three areas. First, to identify the measures of knowledge components such lean, balanced scorecard, global competitive, global culture, innovation, entrepreneur, and succession. Second, this project paper specified various to measure independent variable in leadership attribute there are knowledge, skill, and behavior. And lastly, this project paper predicted the impact of these measures on the performance of leadership qualities based on the results of the questionnaire survey. The study concludes by summarizing the findings with regard to leader performance and finally presents a recommendation to the organization needs and to the future researchers.